Amarna w innych czasach: Amarna in Other Times - Jędraszek, Sławomir (Acta Archaeologica Lodziensia, 2019)
The archaeological remains of Tell el-Amarna (a site in Middle Egypt, which was rediscovered in the early 19th century) are not limited only to the New Kingdom period. Human activity from Middle/Upper Palaeolithic is attested in flint scatters on the desert plain. From the Old Kingdom period fragments of pottery suggest the site served a settlement at this date, probably connected with the Hatnub alabaster (travertine) quarries. The most substantial reoccupation of the site, before the present day, dates to the Late Roman period, when buildings and cemeteries were inserted among the ruins of the New Kingdom city: most notably, the monastery at Kom el-Nana was located in the southern part of the Main City on the line of the Royal Road. In the same period, at Amarna the North Rock Tombs were reoccupied and assigned a new purpose as a settlement for a Christian community.